The effectiveness of cloud-based instant messaging – integrated Islamic psychospiritual program (i-ACT For Life) for the management of psychological distress among at-risk young adults during the Covid-19 Pandemic - Abdul Khaiyom, Jamilah Hanum; Abdul Aziz, Amani Fadzlina; Md. Rosli, Ahmad Nabil; Bahari, Che Amnah; Abdullah, Nur Sakinah Thomas (2023)
Introduction: Mental health issues have increased significantly during COVID-19 pandemic. In Malaysia, a majority of those affected are university students. Efforts are needed to preserve the mental health of at-risk populations. Literature shows religio-spiritual integrated psychological interventions have resulted in more significant psychological and spiritual improvements. The pandemic has challenged the ways of modern healthcare delivery, and remote methods of delivering evidence-based mental healthcare are more important now. Objective: The present study aims to i) elaborates the development of i-ACT for Life, a cloud-based instant messaging Acceptance and Commitment Therapy (ACT)-integrated with an Islamic spiritual program, and ii) examines its effectiveness in managing psychological distress among at-risk young adults in Malaysia during the COVID-19. Method: Purposive sampling was used to recruit university students studying in Malaysia (N=93, 78% female) aged 18-29 years old. The adapted WHO ACT-based module with the elements of Islamic spirituality was used. The program comprises five weekly modules, each corresponded to an ACT core process and was supplemented with Qur’ānic verses, Hadīth, religious/spiritual activities, and spiritual-relevant poems. The program was designed for delivery through cloud-based instant messaging platforms. Participants were randomized to either receive the prevention program (n=46) or be wait-listed (n=47), and were asked to complete assessments at pre-intervention, mid-intervention, post-intervention, and 1-month follow-up. The outcomes assessed were anxiety, stress, depression, self-compassion, psychological flexibility, and resilience. Results: Intention-to-treat analyses using Last Observation Carried Forward reported significant between-group effects at post-intervention and follow-up (p<.05), and a significant overall effect of time across the four-time points (p<.001), for all the outcome measures. Observations of participants' reflections on the Islamic spirituality elements are positive. Conclusions: Findings suggest that the i-ACT for Life, a cloud-based instant messaging program, effectively preserves the mental health of Muslim young adults in Malaysia during the pandemic.